Pengaruh Komunikasi yang Efektif Guru Pendidikan Agama Kristen dan Budi Pekerti terhadap Motivasi Belajar Siswa Kelas VIII SMP Negeri 4 Tarutung Tahun Pembelajaran 2023/2024 - Monica Anastasia Magdalena Rajagukguk; Masniar H. Sitorus; Robinhot Sihombing; Goklas J. Manalu; Frainskoy Rio Naibaho (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the positive and significant influence of effective communication by Christian Religious Education and Character Education teachers on the learning motivation of class VIII students at SMP Negeri 4 Tarutung for the 2023/2024 academic year. The hypothesis of the study is there is a positive and significant influence of effective communication by Christian Religious Education and Character Education teachers on the learning motivation of class VIII students at SMP Negeri 4 Tarutung for the 2023/2024 academic year. The method that used in this study is an inferential quantitative method. The population is all 123 students of class VIII of SMP Negeri 4 Tarutung for the 2023/2024 academic year who are Protestant Christians and samples are determined 40% of the total population as many as 50 people by using random sampling techniques. The study instrument is a closed questionnaire with 39 items, namely 22 items for variable X and 17 items for variable Y. The results of data analysis obtained: a) Testing a positive relation (Product Moment Pearson) obtained a value of rcount = 0.413> rtable (a = 0.05, n = 50) = 0.297. b) Testing a significant relation (t-test) obtained a value of tcount= 3.141>ttable (a=0.05, df=n-2=48)= 2.000. c) Obtain the degree of influence with the regression equation Ŷ= 18,33 + 0,46X. d) Test the hypothesis using the F test to obtain Fcount= 9.823>Ftable (a=0.05, df numerator k-1=1, df denominator=n-2=50-2=48) =4.00. Thus Ha is accepted and H0 is rejected. The study concluded that there was a positive and significant influence of effective communication by Christian Religious Education and Character Education teachers on the learning motivation of class VIII students at SMP Negeri 4 Tarutung for the 2023/2024 academic year.